Masa Jabatan Presiden dan Wakil Presiden: Penambahan Pengaturan pada Keadaan Darurat dan Sirkulasi Periodisasi - Desi Fitriyani; Fitra Arsil; Winda Sari; Nurul Insi Syahruddin (Universitas Serang Raya, 2023)
This paper departs from the problematic arrangements for the term of office of the president and vice president that have been regulated in Article 7 of the 1945 Constitution of the Republic of Indonesia. The article has not accommodated the regulation of the term of office if the country is in a state of emergency and leaves a question regarding the possibility of re-election of the president and vice president who have been elected previously. The purpose of this research is, first, to provide an analysis of the need to regulate the term of office of the president and vice president when the country is in a state of emergency and second, to analyze the need for changes in the circulation of periodicity and tightening of the norms. The type of research used is normative legal research using conceptual and comparative constitutional approaches. The results of the research show that reformulation of the regulation of the term of office of the president and vice president is needed on 2 (two) matters. First, the provisions regarding the term of office of the president and vice president if the country is in a state of emergency which is also carried out by several countries. The urgency of this arrangement can be seen from the experience of emergencies that have occurred in Indonesia. Secondly, it is necessary to circulate periodization and tighten arrangements regarding the possibility of re-election of the president and/or vice president. For accountability, the re-election of the president and/or vice president should only apply if done consecutively. The tightening is intended to close the space for misinterpretation of the existing provisions that the constitution has opened the opportunity for the president and/or vice president to serve more than 2 (two) periods if the partner is a different person.